Anales de la Facultad de Medicina, 1918 - 2008. A recollection, on its 90th anniversary - Pacheco Romero, José (2008)
San Fernando Faculty of Medicine has recently celebrated 150 years of existence, and its official journal Anales de la Facultad de Medicina recalls its presence as a biomedical journal and one of the Faculty’s symbols for the past 90 years. Anales appeared in 1918 due to the need of a journal where medicine, medical education, health, and institutional life articles could be published. Anales is the oldest biomedical journal in Peru and reflects the country’s evolution in medicine, its practice and teaching. Along its 90 years of existence, the most important Peruvian medical researchers, educators and intelectuals have written in Anales. During the last decade, Anales has changed its content in order to comply with the international biomedical journals publication norms. Anales is indexed in Lilacs, Lipecs, Latindex, Red ALyC, and ScIELO Peru, having recently been distinguished by the Universidad Nacional Mayor de San Marcos as the best journal in health sciences.